High frequency Words - "NA" (London DK Children, 2022)
Introducing 100 essential high-frequency words, these cards are perfect for children beginning to learn English as a first or second language. Heard of high frequency words, but don't know where to begin? Don't worry, DK has got you covered! What are high frequency words? These are common words that children are taught to learn by sight either because they appear in such high-frequency (e.g. and, he, go) and being able to instantly recognize them helps children with fluency and independence or the words don't follow normal phonetic sound and spelling patterns. Interactive and engaging, these fun flash cards include: - Introduces 100 essential high-frequency words - Each card features a high-frequency word plus an illustration and simple sentence putting that word into context - On the reverse just the word is shown to help children memorise the words and test their knowledge The perfect accompaniment to English for Everyone Junior: My First English Dictionary, this fun, educational pack of 100 flashcards also functions as a stand-alone product for young learners who are starting to read and speak English, proving suitable for children who are learning English both as a first language and second language. These fun flashcards for kids are ideal for Teachers of English as a foreign language seeking extra resources, as well as parents and grandparents looking to support their child's education further. On one side of each card is an essential high-frequency word (words that frequently appear in text and are best remembered by sight) in large, bold lettering for easy reading. On the reverse, the word is repeated with a simple example sentence and illustration to put the word into context. Children can use the cards to learn the meaning of high-frequency words before memorising the words and testing their knowledge. Five additional cards are packed with suggestions for educational games and activities. Simple to use and fun, these flashcards are made of sturdy laminated cardboard and are suitable for young hands to play with again and again.
Keywords: Flashcards